World atlas for intermediate students (New York : Macmillan/McGraw-Hill, 1991)
Describes, through maps, tables, graphs, and text, the ways people live with each other and the earth.
At head of title: The World around us
Includes index.
LC copy exhibited at 27th IGC International Map and Book Exhibit, 1992.
Keywords: Children's atlases; Atlases